Female artistic gymnastics: From scientific totalitarianism to consumerist totalitarianism (1952-2018) - Plaza Martín, Diana (Hispania Nova, 2019)
By "totalitarian" we usually understand a political system in which freedom is restricted and the state apparatus applies power without limits. However, for some authors like Pier Paolo Pasolini and Marcuse, totalitarianism is also found in the consumption system of advanced capitalism, which imposes a "structural homologation" with a centralizing and alienating power, more powerful than any fascist regime. This structural homogenization has occurred in the process of transforming some sports into shows or consumer products, such as women’s gymnastics.